LOYALITAS PELANGGAN DITINJAU DARI KUALITAS PELAYANAN, KUALITAS PRODUK DAN KEPERCAYAAN PADA USAHA MIKRO KECIL MENENGAH RN SCREEN SOLO - Deva Sulistyo (JURNAL WIDYA GANECWARA, 2020)
The purpose of this study was to prove simultaneously or partially the influence of Service Quality, Product Quality, and Trust on Customer Loyalty at RN Screen Solo. This research uses quantitative descriptive methods. The population in this study was 1000 loyal customers of RN Screen Solo in the past 16 years. Sampling of 100 respondents using incidental sampling technique. Retrieval of using a questionnaire. Analysis technique used is multiple linear regression analysis. This research was conducted from February 2020 to July 2020. F test results (simultaneous) prove that Service Quality, Product Quality, and Trust have a positive and significant effect on RN Screen Solo Customer Loyalty. The t-test results (partial) showed that the variables of Service Quality, Product Quality, and Trust each partially influential on RN Screen Solo Customer Loyalty. The proportion of the dependent variable (Customer Loyalty) explained by the independent variable (Service Quality, Product Quality, and Trust) was 53.1%. The remaining proportion of 46.9% is explained by other variables not present in this study.